Creating a platform for transit-oriented development (TOD) through integrated land use and transport planning in Cape Town: a study of Bellville station - Van Wyk, Carlu (School of Architecture, Planning and Geomatics, 2018)
As urbanisation trends continues and increases across the world, urban trends have seen urban growth take place horizontally, leading to undesired urban sprawl. With the global introduction of the automobile in the 1960's, urban sprawl has been exacerbated with the automobile allowing for the decentralisation of employment, residential, commercial and leisure opportunities away from the Central Business Districts of the city. Due to a multitude of negative social, environmental and economic effects associated with urban sprawl, spatial planning practices have been aimed at reversing this trend and ultimately creating a more compact urban form. In addition to undesired urban sprawl, the use of private vehicles as the dominant mode of transport has also been problematic. In an attempt to address these issues simultaneously, Transit-Oriented Development (TOD) has recently been adopted as a tool with which to achieve transformation of urban forms. This study aims to explore TOD has a tool by assisting to (i) provide a theoretical base and historical perspective of TOD; (ii) provide insight regarding the principles and benefits of TOD that has promoted the use of TOD as a transformative tool; (iii) understand the role of land use and transport planning in providing a platform for the implementation of TOD strategies; (iv) identify cases where TOD has been adopted successfully; (v) understand the role of the legal environment in South Africa with regards to the implementation of TOD strategies; (vi) depicting how the ideal TOD environment could look and function in Cape Town; (vii) understanding how South Africa's legal environment promotes TOD at local level of government in Cape Town and; (viii) what key issues and challenges currently hinder the successful implementation of TOD strategies in Cape Town. This study makes use of a literature review, as well as an empirical study where existing documents (such as spatial development frameworks and integrated transport network plans) are analysed and qualitative and quantitative data is used to explore a number of case studies. From the case studies and additional research it was evident that there is a need for a sound legislative platform which promotes and supports the adoption of TOD at all spheres of government. It was further found that several issues and challenges are made mention of in municipal plans and policies, but that these issues and challenges continue to negatively influence the implementation and success of TOD in Cape Town. Existing legal tools and instruments are not necessarily capable of creating a platform for the implementation of TOD and would thus need to be amended or integrated with other local level strategies. If Cape Town is to successfully use TOD as a tool with which to rectify spatial issues, the legal environment needs to better promote the integration of land use and transport planning in order to encourage densification and to ensure that public transport becomes a viable means of transport in the city. Only once the above mentioned are addressed, can the spatial form of the city be transformed through TOD and future development can contribute to the sustainability of Cape Town.